Hemoglobin function in stored blood - Bunn, H. Franklin (1969)
Serial oxygen dissociation curves were performed on blood units preserved in acid-citrate-dextrose (ACD), ACD-adenine, and ACD-adenine-inosine. Dividing blood from a single donor into two or more bags allowed direct comparison between preservatives. During the 1st wk of storage in ACD, a progressive increase in oxygen affinity was observed. Thereafter, little further change was noted. Oxygen affinity increased even more rapidly during initial storage in ACD-adenine. However, with the inclusion of inosine as a preservative, oxygen affinity remained unaltered during the first 2 wk. Increases in oxygen affinity correlated well with falling levels of red cell 2,3-diphosphoglycerate (2,3-DPG) during storage. No significant changes in glutathione, reduced form (GSH), or A3 (A(I)) hemoglobin levels were noted during the first 3 wk of storage. No significant accumulation of ferrihemoglobin was detected. When blood stored 20 days in ACD or ACD-adenine was incubated with inosine for 60 min at 37°C, 2,3-DPG and adenosine triphosphate (ATP) were resynthesized, and oxygen affinity was decreased. The distribution of 2,3-DPG in fresh and stored red cells appeared to influence experimental values for Hill's n, a measure of heme-heme interaction.